1992
DOI: 10.1177/107769909206900209
|View full text |Cite
|
Sign up to set email alerts
|

Blacks in the News: Television, Modern Racism and Cultural Change

Abstract: Local news may be one vehicle through which television helps, inadvertently, both to preserve and to transform cultural values. Content analysis on the evening news on four Chicago television stations over a lengthy period suggests local television responds to viewing tastes of black audiences. However, data on these Chicago television news programs suggest racism still may be indirectly encouraged by normal crime and political coverage that depict blacks, in crime, as more physically threatening and, in polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
288
2
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 384 publications
(321 citation statements)
references
References 0 publications
17
288
2
14
Order By: Relevance
“…http://www.revistalatinacs.org/068/paper/978_Mexico/12_Carlos.html Página 293 Different studies show the crucial role played by the media in the creation and diffusion of images or social representations of minorities and ethnic groups (Dixon, 2000;Entman, 1992;Seiter, 1986;Tamborini et al, 2000;Gorham, 2009). It is not without cause that it has been stated that "the information that we gain from the mass media results in the production of stereotypes that help us simplify our environment" and, therefore, to "process information" (Dixon, 2000: 62).…”
Section: A Stereotyping Process In the Mediamentioning
confidence: 99%
See 4 more Smart Citations
“…http://www.revistalatinacs.org/068/paper/978_Mexico/12_Carlos.html Página 293 Different studies show the crucial role played by the media in the creation and diffusion of images or social representations of minorities and ethnic groups (Dixon, 2000;Entman, 1992;Seiter, 1986;Tamborini et al, 2000;Gorham, 2009). It is not without cause that it has been stated that "the information that we gain from the mass media results in the production of stereotypes that help us simplify our environment" and, therefore, to "process information" (Dixon, 2000: 62).…”
Section: A Stereotyping Process In the Mediamentioning
confidence: 99%
“…There are studies that have found this priming effect, where individuals http://www.revistalatinacs.org/068/paper/978_Mexico/12_Carlos.html Página 294 exposed to media contents that include stereotyped contents have are more likely to use this same content to process later information than those who have not been exposed. Furthermore, it is difficult to correct the distorted evaluations later on due to the stimuli induced by means of an activation process (Brown-Givens, Monahan, 2005;Domke, 2001;Entman, 1992;Fujioka, 1999;Gorham, 2009;Oliver, Jackson, Moses and Dangerfield, 2004). In contrast to this model of priming, other perspectives assume that the media do not only activate pre-existing stereotypes but also that they can generate new cognitions, as well as changing pre-existing ones (Behm-Morawitz, Ortiz, 2013).…”
Section: A Stereotyping Process In the Mediamentioning
confidence: 99%
See 3 more Smart Citations